Survey of Valuing Stock Options of Selected Publicly Listed Philippine Companies - Dy, Diogenes C. (Philippine Management Review, 2019)
Firms have the flexibility to choose the valuation model and the sources for input variables in determining the fair value of stock options. Thus, firms may be motivated to choose the variables which will result in lower fair value for the stock options. This will translate to lower compensation expense and higher net income. This paper aims to show how selected publicly listed Philippine companies determine the fair value of their stock options.